FAKTOR-FAKTOR YANG MEMPENGARUHI COST OF DEBT PERUSAHAAN - Merkusiwati, Ni Ketut Lely Aryani; Suaryana, I Gusti Ngurah Agung; Ulianti, Ni Putu Lola; Putra, Agus Erik Wistika (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.01.TAHUN.2024, 2024)
This study aims to empirically examine the influence of factors that affect the company's cost of debt. Factors that affect the cost of debt include tax avoidance, institutional ownership, profitability, operating cash flow and leverage, institutional ownership, profitability, operating cash flow and leverage. The phenomenon of The phenomenon of this research is the increase in companies that are unable to pay debts, thereby increasing the cost of debt. This increasing the cost of debt. Companies that are in the spotlight today are state-owned companies or SOEs that are in debt for various reasons so that it becomes a serious problem reasons so that it becomes a serious problem. The high cost of debt for The high cost of debt for the company will increase the possibility of the company going bankrupt. This study tested 22 research samples for 4 years. The method used is multiple linear regression analysis. The results prove that tax avoidance tax avoidance has no significant effect on Cost of Debt (COD), Institutional Ownership has no significant effect on COD, Profitability has no significant effect on COD. Institutional Ownership has no significant effect on COD, Profitability has a significant negative effect on COD, Operating Cash Flow, Operating Cash Flow has a significant positive effect on COD, Leverage has a significant positive effect on COD significant positive effect on COD.